Carbothermal synthesis of metal-functionalized nanostructures for energy and environmental applications. Issue 25 (7th July 2015) - Shen, Yafei
<x xml:space="preserve">Abstract</x> Carbothermal reduction could be employed as a facile technology for the synthesis of various novel materials, especially transition-metal-functionalized nanostructures.